Una nueva propiedad intelectual para el siglo xxi. Focos, críticas y propuestas puntuales para una futura regulación de los bienes inmateriales (2018)
The consultation of the state of the art seems to suggest that the regulation of internet, insofar as it concerns intellectual property, is such an overwhelming challenge that it has slowly taken an anomie appearance that is not only dangerous, but depressive, if seen from the perspective of the network author. The text analyzes the problem and proposes specific solutions in various stages of time. Comparative law and legal history are inputs that have been used, trying to suggest evidence that seem easy to apply, despite the resistance of the majority of the doctrine’s opinion.